An activatable and tumor-targeting NIR fluorescent probe for imaging of histone deacetylase 6 in cancer cells and in vivo. Issue 12 (19th January 2022) - Li, Min; Liu, Jin; Chen, Xuefei; Dang, Yijing; Shao, Yong; Xu, Zhiai; Zhang, Wen
Abstract : We designed an activatable NIR fluorescent probe for imaging of histone deacetylase 6 in cancer cells and in vivo . Abstract : An activatable and tumor-targeting near-infrared (NIR) fluorescent probe CyAc-RGD was synthesized for the imaging of histone deacetylase 6 (HDAC6). The probe exhibited higher sensitivity and specificity for HDAC6 detection in cancer cells. Moreover, CyAc-RGD demonstrated good tumor-targeting ability and realized HDAC6 imaging in vivo .